The incentive effects of the overlapping project structure in credit markets - Niinimäki, Juha-Pekka (Elsevier, 2025)
In this theoretical paper, we examine the risk-shifting problem between lenders and a firm running projects in two different environments. In a synchronous environment, the firm introduces two new 2-period projects that both begin and end on the same date and hence have a new start date in odd-numbered periods. In an asynchronous environment, the firm introduces one new 2-period project in every period: This process creates an overlapping structure for the projects. We show that the set of parameters that allow for reputation-supported lending is larger if projects are asynchronous rather than synchronous. The findings can be generalized to other forms of moral hazard.